Synthesis and in vitro biological evaluation of metal complexes containing Pyridine - Minakshi Kumari; Mohd. Hussain; Aditay Kumar; Mamta khatak; Mohd. Isfaq; Mayank Mehendiratta; Mahesh kumar (Revista Electronica de Veterinaria, 2024)
In the present study, metal complexes containing pyridine have been synthesized and characterized by physicochemical and spectral means. Broth microdilution (96 well microtiter plate) method was used to evaluate antimicrobial activity of the synthesized compounds against Gram positive bacteria (B. subtilis), Gram negative bacteria (E. coli) and fungal species (A.terrus & A.niger ) using cefadroxil (antibacterial) and fluconazole (antifungal) as standard drugs. Among the synthesized compounds, chalcone ligand C1 showed good antifungal activity. against A.terrus & A.niger (MIC =3.12µg/ml.) while complex KP1 showed significant activity against E. coli (MIC=1.56µg/ml) , A. niger (MIC=3.12µg./ml) and A. terrus (MIC=1.56µg/ml). Complex KP7 showed significant activity against B.subtilis and E.coli.(MIC = 3.12 µg/ml.). Antioxidant activity of the synthesized compounds was determined using D.P.P.H. assay method. Complex KP2 showed excellent antioxidant activity (48.46). The order of antioxidant activity showed the increase in antioxidant activity KP2>KP3> KP6>KP5>KP4>>KP7>C2>KP1>KP8>C1